A cross sectional study to determine the reasons for non-utilization of reproductive and child health services in district Etawah - Singh, Vaibhav; Srivastava, Dhiraj Kumar; Jain, Pankaj Kumar; Kumar, Sandip; Shukla, Sushil Kumar; Singh, Nishant; Baranwal, Harshita (International Journal Of Community Medicine And Public Health, 2020)
Background: The utilization of social services, including health services, has never been equitably distributed in the society. Cost, distance, attitude of health providers, and other factors put the secondary care and private sector facilities out of reach of most of the poor residents. The socioeconomic factors also have a complex relationship with some of the supply factors, and often in the scarcity of good data, it is very difficult to explain the poor utilization of reproductive and child health (RCH) services. Methods: A cross sectional study conducted on 80 recently delivered women at home in the villages covered under the selected subcentre to interview all recently delivered women to find out the reasons for non-utilization of RCH services. The data was collected by using pre designed semi-structured questionnaire. Results: Most of the participants belong to age group of 20 to 24 (55%) and joint family (51.3%). Main reason for not having institutional delivery was found to be long waiting time in hospital/lack of proper facilities (50%) followed by non-cooperative hospital staff (36.2%). The study showed that most common reason for not getting money under JSY was found to be non-issuance of JSY card (33.3%) and non-cooperative hospital staff (33.3%). It was found that non utilisation of contraceptive services was mainly due to objection by husband (45.5%). Conclusions: This study revealed lack of knowledge, no felt need and financial constraints as the most common reason for not utilizing the different RCH services.